AN ANALYSIS OF THE IMPLEMENTATION OF THE FIVE MONTESSORI AREAS IN GAMELAN EDUCATION - Maria Vianney Ratriana Pertiwi Larasati; Fu’adi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study aims to describe the implementation of the five Montessori areas in gamelan learning. The study employed a qualitative descriptive approach involving eighth-grade students of Stella Duce 2 Junior High School Yogyakarta as the research subjects. Data were collected through observations and documentation in the form of Exploration and Reflection Worksheets based on the Montessori areas. The findings indicate that all five Montessori areas can be implemented in gamelan learning through various authentic activities. The practical life area was reflected in group collaboration and the distribution of instrumental roles. The sensorial area was evident in sound exploration activities and the development of listening sensitivity. The mathematics area was implemented through the understanding of rhythmic patterns and song structures. The language area emerged through discussions, musical communication, and learning reflections. The cultural area was manifested in the understanding of togetherness, etiquette, and appreciation of gamelan as a cultural heritage. The findings suggest that the characteristics of gamelan learning are aligned with Montessori principles and support holistic learning experiences in music education.